THE SENSE OF EMPOWERMENT AMONG PARENTS OF CHILDREN WITH AUTISM - Banasiak, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of this study was to examine the level of a sense of empowerment among mothers and fathers of children with autism. The relationship between a sense of empowerment and socio-demographic variables characterising the respondents including the parents was also analysed. Among the participants, there were 74 parents of autistic children (39 mothers, 35 fathers), 77 parents of children with Down syndrome (40 mothers, 37 fathers) as well as 80 parents of typically developing children (40 mothers, 40 fathers). Two statistical tools, namely the non-parametric Mann-Whitney U test and Kruskal-Wallis test, were employed in this study. The results show a higher level of a sense of empowerment when it comes to the evaluation of own knowledge and competences in mothers of autistic children than in mothers of children with Down syndrome, contrary to fathers of autistic children whose level of a sense of empowerment is lower within the said scope compared with fathers of children with Down syndrome.